Ivy + Bean what's the big idea? - Barrows, Annie; Blackall, Sophie (San Francisco : Chronicle Books, 2010)
When all the second grade students must enter the science fair, which has global warming as its theme, best friends Ivy and Bean team up to create an unusual project.
Keywords: Science projects -- Juvenile fiction; Science fairs -- Juvenile fiction; Schools -- Juvenile fiction